2015
DOI: 10.1103/physrevx.5.031021
|View full text |Cite
|
Sign up to set email alerts
|

Electron Dynamics in the Core-ExcitedCS2Molecule Revealed through Resonant Inelastic X-Ray Scattering Spectroscopy

Abstract: We present an experimental and theoretical study of resonant inelastic x-ray scattering (RIXS) in the carbon disulphide CS 2 molecule near the sulfur K-absorption edge. We observe a strong evolution of the RIXS spectral profile with the excitation energy tuned below the lowest unoccupied molecular orbital (LUMO) absorption resonance. The reason for this is twofold. Reducing the photon energy in the vicinity of the LUMO absorption resonance leads to a relative suppression of the LUMO contribution with respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…27,28 Our study contributes to demonstrating how time-resolved photoelectron spectroscopy complements other x-ray based probes of molecular gas-phase dynamics using ion spectroscopy, [29][30][31][32] x-ray absorption spectroscopy, [33][34][35][36][37] and x-ray scattering, 38 and it relates to core-hole induced dynamical effects in steady-state x-ray spectroscopy. 30,31,[39][40][41][42] Our study extends the demonstrated capabilities of time-resolved photoelectron spectroscopy with optical probe pulses, 18,43 and it shows how x-ray photoelectron spectroscopy complements other x-ray methods for the investigation of molecular dynamics. [44][45][46][47][48][49][50]…”
Section: Fig 1 (A)supporting
confidence: 58%
“…27,28 Our study contributes to demonstrating how time-resolved photoelectron spectroscopy complements other x-ray based probes of molecular gas-phase dynamics using ion spectroscopy, [29][30][31][32] x-ray absorption spectroscopy, [33][34][35][36][37] and x-ray scattering, 38 and it relates to core-hole induced dynamical effects in steady-state x-ray spectroscopy. 30,31,[39][40][41][42] Our study extends the demonstrated capabilities of time-resolved photoelectron spectroscopy with optical probe pulses, 18,43 and it shows how x-ray photoelectron spectroscopy complements other x-ray methods for the investigation of molecular dynamics. [44][45][46][47][48][49][50]…”
Section: Fig 1 (A)supporting
confidence: 58%
“…61 Furthermore, rearrangement processes observed herein are the result of extremely fast (femtosecond or attosecond regime) chemical reactions. 62 The [CH n ] + /[S] + coincidences appear as well-dened and hydrogen-resolved islands, each one with two maximum regions, as shown in Fig. 3(a) The mechanisms depicted in eqn (6) and 7are also in agreement with the previous work by Butler, 58 which observed that the release of neutral S species competes with the direct H 3 CS-SCH 3 bond cleavage.…”
Section: Ion-ion Coincidences and Fragmentation Mechanismssupporting
confidence: 87%
“…As the probability of radiative relaxation of core-excited atoms increases with atomic number, both RIXS and RAS become equally relevant in the hard x-ray regime [5][6][7][8][9][10][11][12][13][14]. However, the major difference between these techniques appears in the electronic final states reached upon relaxation.…”
mentioning
confidence: 99%